The Comparison of Health Insurance between Indonesia and other Middle-Income Countries - Resa Listiani; Kania Rizqita Dewi; Jahira Fajri Madani; Siti Humaira Syarif (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2023)
Health insurance is a form of financial protection that allows a person to obtain financial protection when they need health care. In middle-income countries, health insurance schemes are divided into three types: community-based health insurance, voluntary health insurance, and compulsory health insurance. Implementation varies from country to country depending on conditions and policies. The purpose of this study is to compare Indonesia's health insurance system with other middle-income countries in terms of coverage, services, and financial sustainability. By conducting this comparison, it is hoped that the most effective and efficient health insurance model can be found. This research uses the literature review method with search engines used in literature searches including Google Scholar and PubMed with the keywords Health, Health insurance, Indonesia, middle-income countries, Health system, Health services, and Health policy. The resulting articles were selected based on publications published between 2018 and 2023. The results show that the comparison of the health insurance system in Indonesia with other middle-income countries is not much different, because the aspects of financing, membership, availability, accessibility, and quality of health services are still challenges that need to be addressed by the government and society. However, each country has different policies and programs.